Analisis Sea Level Anomaly Dengan Menggunakan Data Multi Satelit Altimetri Di Perairan Indonesia - I Gusti Putu Ary Wedangga; I Gusti Bagus Sila Dharma; I Dewa Nyoman Nurweda Putra (Journal of Marine and Aquatic Sciences, 2022)
Global warming become one of the problems currently faced by the world. In general, global warming is a phenomenon where the average temperature of the earth has increased, both the temperature of land, atmosphere, and sea. As a result, global warming can cause global climate change, and sea level rise. Sea level rise is a condition where the increasing of sea water volume that caused by melting of the ice caps or thermal expansion. This study used Sea Level Anomaly (SLA) dan Sea Surface Temperature (SST) data with 1/4° x 1/4° spatial resolution and daily temporal resolution for 10 years (2008 - 2018). The study was conducted in Indonesian waters within coordinates of 10°N – 13°S dan 93°E – 141°E, with 8 areas focused on analyzing sea level anomaly trends. During the period 2008 - 2018 there was a positive trend of sea level anomaly at all research area. The highest sea level rise occurred in area B (Sulawesi Sea) of 4.788 cm with a rate of increase of 0.479 cm / year. In general there was an average increase of 3.686 cm in Indonesian waters with a rate of increase of 0.369 cm / year.